Decreasing employees' work stress by a participatory, organizational level work stress prevention approach: a multiple-case study in primary education - Maartje C. Bakhuys Roozeboom; Roosmarijn M. C. Schelvis; Irene L. D. Houtman; Noortje M. Wiezer; Paulien M. Bongers (BMC, 2020)
Abstract Background Work stress is an important problem among employees in education in the Netherlands. The present study aims to investigate the effects of a participatory organizational level work stress prevention approach to reduce (quantitative) job demands, increase resources (i.e. autonomy, supervisor and coworker support) and to reduce work stress and increase job satisfaction of employees in primary education. Methods This study makes use of a multiple case study research design. The stress prevention approach is implemented at 5 primary schools and questionnaires were filled out by 119 employees of the 5 schools at baseline and 1 year later, measuring job demands, resources, work stress, job satisfaction and implementation factors. Results Multilevel analyses showed a significant decrease in job demands and a significant increase in job satisfaction between baseline and follow up. In addition, employees that were more satisfied with the communication about the intervention showed more improvements in autonomy and job satisfaction. However, employees reporting an increased dialogue in work stress between employees and management showed a smaller decrease in job demands. Conclusion The study shows a decrease in job demands and an increase in job satisfaction in the schools that implemented a stress prevention approach. Results of the study underline the importance of communication about the intervention as part of the implementation process, impacting the effectiveness of the intervention to improve autonomy and job satisfaction. Trial registration ISRCTN registry, study ID: ISRCTN14697835 , registration date: 11-10-2019 (retrospectively registered).